(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
Objective: To determine the functional outcome of posterior triceps muscle sparing versus muscle splitting approach in supracondylar humerus fracture in children. Methods: This prospective randomized controlled study was conducted from September 2014 to March 2016. Thirty-eight patients from pediatric age group (5 to 14 years) and either gender side with the delayed presenting (4.97± 1.69 days) supracondylar humerus fracture [SHF], Gartland type III. Patients were randomly divided into group A (triceps muscle sparing approach) and group B (triceps muscle splitting) each having 19 patients, for Open Reduction and Internal Fixation [ORIF]. Functional outcome was determined in outpatient department on follow up using Gruber and Healy scoring system. Results: Out of 38 patients, 24 (63.1%) were male and 14 (36.8%) were females. The mean age of the patients in our study was 9.13± 4.97 years and the mean delay in presentation was 4.97± 1.69 days. These patients were randomly divided into group A and group B, each having 19 patients. Group A patients underwent triceps muscle sparing technique while group B had triceps muscle splitting technique. The success of either procedure was assessed by functional outcome using Gurber and Healy score on progressive follow ups in outpatient department. The fractures in group A united radiologically in a mean duration of 7.52 ± 1.46 weeks, while in group B the mean duration of union was 8.12 ± 1.34 weeks. We found that the muscle sparing approach had excellent functional outcome in 18 (94.73%) patients as compared to 09 (47.36%) patients in muscle splitting (group B) which was significant, p value < 0.05. Conclusion: Supracondylar humerus fractures requiring open reduction and fixation in children with triceps muscle sparing technique had better functional outcome than triceps muscle splitting approach.